Effect of handling and crowding on the susceptibility of Atlantic salmon (Salmo salar L.) to Lepeophtheirus salmonis (Krøyer) copepodids. Issue 3 (28th October 2020) - Delfosse, Cyril; Pageat, Patrick; Lafont‐Lecuelle, Céline; Asproni, Pietro; Chabaud, Camille; Cozzi, Alessandro; Bienboire‐Frosini, Cécile
Abstract: Lepeophtheirus salmonis is an ectoparasite causing economic concerns in Atlantic salmon farming. Salmon lice infestation management methods can be stressful and impact fish welfare. This work investigated the stress effect on the attachment of L. salmonis copepodids to Atlantic salmon through two approaches: (a) handling by netting and air exposure (acute stress), and (b) crowding with restricted surface access in a tank (chronic stress). In the first experiment, we compared the number of attached L. salmonis and cortisol levels between a group of handled salmon and a control group. In the second experiment, a group of densely packed salmon was compared to a control group based on the number of attached copepodids, cortisol levels and neutrophil:lymphocyte ratios. Handled salmon showed significantly higher plasma cortisol levels ( p < .001) and more attached copepodids ( p = .01) than control salmon. Conversely, the cortisol level and number of attached copepodids were not significantly different between the densely packed and control salmon ( p > .05). The neutrophil:lymphocyte ratio was significantly higher ( p = .0014) in the densely packed salmon than in the control salmon. Handling salmon increased their risk of infestation by L. salmonis . This has implications for reinfestation rates following delousing treatments in commercial salmon aquaculture, which often involve crowding and handling salmon.